Pendekatan Semiotika Dalam Studi Islam (Telaah Makna Semiosis Syirik) - Hafis Khoerul Mahfudz (JURNAL INDO-ISLAMIKA, 2011)
This paper will discuss the meaning of the word semiosis syirik in the hadith. This paper is a qualitative study using the Umberto Eco semiotic approach. Umberto Eco is a philosopher, essayist, semiotic expert, critic of literary works, and novelist. His most famous work is The Name of the Rose, a story that combines intellectual fictional mysteries, biblical analysis, and literary theory. The sources of this paper are books and journals that are relevant to the theme of the writing. The formulation of the problem in this paper is: what is the meaning of shirk semiosis?